Aprepitant: an antiemetic drug, contributes to the prevention of acute lung injury with its anti-inflammatory and antioxidant properties. (23rd June 2021) - Kose, Duygu; Un, Harun; Ugan, Rustem Anil; Halici, Zekai; Cadirci, Elif; Tastan, Tugba Bal; Kahramanlar, Aysenur
Abstract: Objectives: We investigated, the effects of aprepitant (APRE) on the lung tissues of rats with an experimental polymicrobial sepsis model (CLP: cecal ligation and puncture) biochemically, molecularly and histopathologically. Methods: A total of 40 rats were divided into 5 groups with 8 animals in each group. Group 1 (SHAM), control group; Group 2 (CLP), cecal ligation and puncture; Group 3 (CLP + APRE10), rats were administered CLP + 10 mg/kg aprepitant; Group 4 (CLP + APRE20), rats were administered CLP + 20 mg/kg aprepitant; and Group 5 (CLP + APRE40), rats were administered CLP + 40 mg/kg aprepitant. A polymicrobial sepsis model was induced with CLP. After 16 h, lung tissues were taken for examination. Tumour necrosis factor α (TNF-α) and nuclear factor-kappa b (NFK-b) messenger ribonucleic acid (mRNA) expressions were analysed by real-time PCR (RT-PCR), biochemically antioxidant parameters such as superoxide dismutase (SOD) and glutathione (GSH) and oxidant parameters such as malondialdehyde (MDA) and lung damage histopathologically. Key findings and conclusions: The GSH level and SOD activity increased while the MDA level and the expressions of TNF-α and NFK-b were reduced in the groups treated with APRE, especially in the CLP + APRE40 group. The histopathology results supported the molecular and biochemical results.